Triggered Immune Response Induced by Antigenic Epitopes Covalently Linked with Immunoadjuvant-Pulsed Dendritic Cells as a Promising Cancer Vaccine - Chumeng Chen; Mohanad Aldarouish; Qilong Li; Xiangzhen Liu; Feng Han; Hui Liu; Qijun Qian (Journal of Immunology Research)
The success of peptide-based dendritic cell (DC) cancer vaccines mainly depends on the utilized peptides and selection of an appropriate adjuvant. Herein, we aimed to evoke a broad immune response against multiple epitopes concurrently in the presence of immunoadjuvant. Three synthetic HLA-A∗0201-restricted peptides were separately linked with HMGB1-derived peptide (SAFFLFCSE, denoted as HB100-108) as immunoadjuvant via double arginine (RR) linker and loaded onto human monocyte-derived DCs. Peptide uptake was detected by immunofluorescence microscopy and flow cytometry. The maturation and activation status of pulsed DCs were monitored by detection of the expression of specific markers and released cytokines. The ability of peptide-pulsed DCs to activate allogeneic T cells has been assessed by a degranulation assay and detection of secreted cytokines. The lytic activity of effector T cells against cancer cells in vitro was analyzed by a lactate dehydrogenase (LDH) assay. Results revealed that DCs efficiently take up peptides+HB100-108 and expressed higher levels of surface markers (HLA-ABC, HLA-DR, CD80, CD86, CD83, CD40, and CCR7) and proinflammatory cytokines (IL-6, IFN-γ, TNF-α, and IL-12) than control DCs, free peptide-pulsed DCs, and free HB100-108-pulsed DC groups. Moreover, peptides+HB100-108/pulsed DCs were capable of activating allogeneic T cells and enhance their lytic activity against a pancreatic cancer cell line (PANC-1) in vitro. These findings suggest that antigenic peptides covalently linked with HB100-108/pulsed DCs could be a promising strategy to improve the current DC-based cancer vaccines.